2008
DOI: 10.1089/sus.2008.9990
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Certification of Higher Education for Sustainable Development

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 2 publications
0
31
0
4
Order By: Relevance
“…The AISHE system has been used to assess sustainability education in a number of PSE institutions across Europe, while the AUA has been used to examine the uptake of sustainability in education, governance, research and community engagement within PSE institutions located in the Asia-Pacific region. In using AISHE, Roorda and Martens [64] notice that sustainability in education is best assessed within separate programs or departments of a given university, due to the methodological and developmental differences that exist between faculties within a university. They go on to note that this can make cross-curricular comparison of sustainability difficult, even within the same institution.…”
Section: Measuring Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The AISHE system has been used to assess sustainability education in a number of PSE institutions across Europe, while the AUA has been used to examine the uptake of sustainability in education, governance, research and community engagement within PSE institutions located in the Asia-Pacific region. In using AISHE, Roorda and Martens [64] notice that sustainability in education is best assessed within separate programs or departments of a given university, due to the methodological and developmental differences that exist between faculties within a university. They go on to note that this can make cross-curricular comparison of sustainability difficult, even within the same institution.…”
Section: Measuring Sustainabilitymentioning
confidence: 99%
“…The researchers note businesses were better at tying efficiency policies to local sustainability initiatives in the communities they are embedded in, while critiquing some universities for viewing their non-profit status as a license to be inefficient with resources. Roorda and Martens [64] report that quality management tools developed by the business world and utilized by PSE institutions to assess environmental sustainability in Europe include tools developed by the International Organization for Standardization (ISO) and the European Foundation for Quality Management (EFQM). In comparing university auditing of sustainability practice for universities in New Zealand, Fisher [73] suggests that the ISO 14000 series of environmental standards would be useful for campuses commencing sustainability reviews.…”
Section: Measuring Sustainabilitymentioning
confidence: 99%
“…These indexes, however, should be instruments orientated towards the particularities of the higher education institution, for example, the Graphical Assessment of Sustainability in Universities -GASU (Lozano, 2006), the Sustainability Tool for Auditing Universities Curricula in Higher Education -STAUNCH (Lozano, 2010), the Framework-Level-Actors -FLA Analysis (Ferrer-Balas, Buckland, Mingo, 2007) and the Auditing Instrument for Sustainability in Higher Education -AISHE (Roorda, 2001;2008). Shriberg (2002) presented in his article an outlook of the strengths and weaknesses of the assessment tool and concluded that it is necessary in the future to think about a universal assessment tool which can facilitate the ranking of universities in terms of levels of sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…as a self-assessment tool (Roorda, 2004;2008). Every university is free to do so, as all necessary equipment, such as the AISHE book (Roorda, 2001) and the computer application ' AISHE Reporter', can simply be downloaded.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing sustainable development requires that there is an accepted understanding of what this means for universities. One of the promising approaches mentioned by [6] is the Assessment Instrument of Sustainability in Higher Education (AISHE) that defines university sustainability using the modules of identity, operations, education, research and society [7][8][9][10]. The AISHE-model provides a proposed operationalization of sustainability that clearly states responsibilities within the core activities of education and research and also in work with society, while referring to the Brundtland commission definition and the Triple Bottom Line.…”
Section: Introductionmentioning
confidence: 99%